Level of Anxiety among Tuberculosis Patients in Selected Chest Clinics in Mombasa County, Kenya - Okello, Osoo; Oteyo, John (Global Journal of Health Sciences, 2023)
Purpose: The aim of this study was to explore the levels of anxiety among Tuberculosis patients in selected chest clinics in Mombasa County, Kenya. Methodology: The research adopted correlational design. The study was conducted in selected three chest clinics in Mombasa County. All tuberculosis patients diagnosed with active tuberculosis disease who are registered and collect their medicines from selected chest clinics in Mombasa County was the targeted population. Convenience sampling was applied because only patients on TB treatment within the period of study were interviewed. Simple random sampling was used to select participants from each stratum to be involved in the study. The sample size involved 200 TB patients. The research adopted questionnaire which consisted of both open ended and closed ended questions to collect data. The study adopted a questionnaire in collection of data. The questionnaire contained both open ended and close ended questionnaire. The researcher used descriptive statistics to help in organizing of data and it would also be helpful in summarizing of data for ease of making interpretations. Statistical Package for Social Science version 25 aided in data analysis. Frequency, percentages and moment was used in data analysis. Findings: From the study it was also clear that 17.3% of those respondents with moderate non-adherence had severe anxiety, 91% reported that anxiety affected their non-adherence. Side effects of the medication, long duration of treatment and misinformation were the main triggers of anxiety at 75%, 16.3% and 8.7% respectively. The analysis of data showed that 51.3% of the respondents experienced mild anxiety, 27.2% moderate anxiety while 21.5% had severe anxiety. Some of the factors that the respondents stated triggered their anxiety included; side effects of the medicine 75%, 16.3% long duration of therapy and 8.7% said misinformation about Tb treatment made them become anxious. Unique Contribution to Theory, Practice and Policy: The Care Seeking Behaviour may be used to anchor future studies relating to the level of anxiety to treatment among TB patients. According to the theory, a patient is motivated to seek treatment for a certain ailment when they have positive feelings about the available treatment options and they have been reassured thus have reduced anxiety. The study recommended that there is need for screening and intervention of mental health conditions like anxiety and depression among TB patients to mitigate non-adherence of TB treatment. This should be done through screening, assessment and use of evidenced based psychological intervention. There is need for community awareness to demystify diagnosis and treatment of TB, mitigate stigma and discrimination associated with TB and promotion of social support to TB patients in seeking and adhering to TB treatment.